Photocatalytic Degradation of Bacterial Lipopolysaccharides by Peptide-Coated TiO2 Nanoparticles - Caselli, Lucrezia; Du, Guanqun; Micciulla, Samantha; Traini, Tanja; Sebastiani, Federica; Diedrichsen, Ragna Guldsmed; Köhler, Sebastian; Skoda, Maximilian W.A.; van der Plas, Mariena J.A.; Malmsten, Martin (ACS Applied Materials and Interfaces, 2024)
In this study, we report the degradation of smooth and rough lipopolysaccharides (LPS) from Gram-negative bacteria and of lipoteichoic acid (LTA) from Gram-positive bacteria by peptide-coated TiO2 nanoparticles (TiO2 NPs). While bare TiO2 NPs displayed minor binding to both LPS and LTA, coating TiO2 NPs with the antimicrobial peptide LL-37 dramatically increased the level of binding to both LPS and LTA, decorating these uniformly. Importantly, peptide coating did not suppress reactive oxygen species generation of TiO2 NPs; hence, UV illumination triggered pronounced degradation of LPS and LTA by peptide-coated TiO2 NPs. Structural consequences of oxidative degradation were examined by neutron reflectometry for smooth LPS, showing that degradation occurred preferentially in its outer O-antigen tails. Furthermore, cryo-TEM and light scattering showed lipopolysaccharide fragments resulting from degradation to be captured by the NP/lipopolysaccharide coaggregates. The capacity of LL-37-TiO2 NPs to capture and degrade LPS and LTA was demonstrated to be of importance for their ability to suppress lipopolysaccharide-induced activation in human monocytes at simultaneously low toxicity. Together, these results suggest that peptide-coated photocatalytic NPs offer opportunities for the confinement of infection and inflammation.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.
Keywords: antimicrobial peptide; lipopolysaccharide; oxidation; photocatalysis; TiO